Environmental hotspots of lactic acid production systems - Ögmundarson, Ólafur; Sukumara, Sumesh; Laurent, Alexis; Fantke, Peter (Global change biology. Bioenergy, 2020)
Using selected bio‐based feedstocks as alternative to fossil resources for producing biochemicals and derived materials is increasingly considered an important goal of a viable bioeconomy worldwide. However, to ensure that using bio‐based feedstocks is aligned with the global sustainability agenda, impacts along the entire life cycle of biochemical production systems need to be evaluated. This will help to identify those processes and technologies, which should be targeted for optimizing overall environmental sustainability performance. To address this need, we quantify environmental impacts of biochemical production using distinct bio‐based feedstocks, and discuss the potential for reducing impact hotspots via process optimization. Lactic acid (LA) was used as an example biochemical derived from corn, corn stover, and macroalgae (Laminaria sp.) as feedstocks of different technological maturity. We used environmental life cycle assessment (LCA), a standardized methodology, considering the full life cycle of the analyzed biochemical production systems and a broad range of environmental impact indicators. Across production systems, feedstock production and biorefinery processes dominate life cycle impact profiles, with choice in energy mix and biomass processing as main influencing aspects. Results show that uncertainty decreases with increasing technological maturity. When using Laminaria sp. (least mature among selected feedstocks), impacts are mainly driven by energy utilities (up to 86%) due to biomass drying. This suggests to focus on optimizing or avoiding this process for significantly increasing environmental sustainability of Laminaria sp.‐based LA production. Our results demonstrate that applying LCA is useful for identifying environmental impact hotspots at an earlier stage of technological development across biochemical production systems. With that, our approach contributes to improving the environmental sustainability of future biochemical production as part of moving toward a viable bioeconomy worldwide. Environmental performance of biochemical production is largely a function of the chosen feedstock system. The present study demonstrates how life cycle assessment (LCA) can be applied to pinpoint environmental hotspots specific for producing lactic acid from three selected biofeedstocks, namely corn, corn stover, and macroalgae. Results highlight that feedstock production and biorefinery processes dominate life cycle impact profiles across feedstocks, mainly driven by choice in energy mix and biomass processes, especially biomass drying. We demonstrate that applying LCA is useful for identifying environmental impact hotspots at an early stage of technological development across biochemical production systems.